The impact of crisis manifestations on the trends of socio–economic indicators of the Vladimir region - K. A. Vlasenko (Путеводитель предпринимателя)
: Over the past few years, the Russian Federation has been repeatedly exposed to external negative influences. The destabilizing effects of the pandemic and sanctions require special attention from the Government of the country. Various anti–crisis measures are being developed, including measures to support the most vulnerable socio–economic systems.The stability of the country’s economy to crisis manifestations depends on the level of economic development of individual subjects. Accordingly, it is necessary to systematically analyze their trends and monitor changes.This article presents the indicators of the Vladimir region. The dynamics of the population and average per capita income for the period 2010–2021 are graphically presented, as well as the forecast up to 2025. The article examines the change in the growth rates of the main socio[economic indicators for three periods: pre–crisis and crisis. To systematize the studied parameters, a factor analysis was carried out, which allowed them to be divided into 3 groups: fixed assets, the human factor and innovative activity. A high direct correlation was revealed between the latter and GRP.